2005
DOI: 10.1677/joe.1.06181
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of central versus peripheral effects of estradiol in ovariectomized mice

Abstract: It is generally believed that estrogens exert their bone sparing effects directly on the cells within the bone compartment. The aim of the present study was to investigate if central mechanisms might be involved in the bone sparing effect of estrogens. The dose-response of central (i.c.v) 17 -estradiol (E2) administration was compared with that of peripheral (s.c.) administration in ovariectomized (ovx) mice. The dose-response curves for central and peripheral E2 administration did not differ for any of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…20 Ovariectomy was performed 2 weeks before injury and E2-PLGA, saline-PLGA, or E2 pellets (Innovative Research of America, Sarasota, FL, USA) were administered at the designated injury sight one week later (i.e., 1 week before injury); E2-PLGA and saline PLGA were administered via subcutaneous injection, and the E2 pellets were subcutaneously implanted. Cyclopamine (50 mg/kg per day) and the estrogen receptor antagonist ICI 182,780 21 (8.3 mg/kg per day; Tocris Cookson Ltd, Bristol, UK) were intraperitoneally injected once daily from 2 days (cyclopamine) or 3 days (ICI) before injury until sacrifice. Serum E2 levels were determined with an E2-ELISA kit (Cayman Chemical, Ann Arbor, MI, USA) as directed by the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…20 Ovariectomy was performed 2 weeks before injury and E2-PLGA, saline-PLGA, or E2 pellets (Innovative Research of America, Sarasota, FL, USA) were administered at the designated injury sight one week later (i.e., 1 week before injury); E2-PLGA and saline PLGA were administered via subcutaneous injection, and the E2 pellets were subcutaneously implanted. Cyclopamine (50 mg/kg per day) and the estrogen receptor antagonist ICI 182,780 21 (8.3 mg/kg per day; Tocris Cookson Ltd, Bristol, UK) were intraperitoneally injected once daily from 2 days (cyclopamine) or 3 days (ICI) before injury until sacrifice. Serum E2 levels were determined with an E2-ELISA kit (Cayman Chemical, Ann Arbor, MI, USA) as directed by the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Rats receiving either EE or ICI treatment alone were also administered vehicle at the appropriate time points. Statistically significant changes in TST were observed among treatment groups [F (5,45) ϭ 13.43; P Ͻ 0.0001] (Fig. 3A).…”
Section: Ici Blocks Estrogenic Actions In the MD Model Of Hot Flush Bmentioning
confidence: 99%
“…Reportedly, the compound does not cross the blood-brain barrier (BBB) (1)(2)(3), and has been used in preclinical studies to understand the biological roles of estrogen receptor (ER) signaling and distinguish peripheral vs. central effects of estrogens (1)(2)(3)(4)(5). Results from clinical studies suggest that ICI (fulvestrant) may be useful in treating advanced, hormone receptor-positive breast cancer in postmenopausal women (6,7).…”
mentioning
confidence: 99%
“…However, indirect actions are also evident. Namely, a recent study demonstrated that estrogen signaling in the brain contributes to the regulation of the skeleton, with intracerebroventricular estrogen replacement in mice providing at least 1/3 of the total cancellous bone formation stimulated by estrogen supplementation [79]. Part of this regulation could conceivably take place via modulation of central NPY expression.…”
mentioning
confidence: 99%